Cultural Mapping of the Heritage Districts in Medan, North Sumatra. (March 2017) - Fitri, I; Ratna,; Sitorus, R; Affan, M
Abstract: Medan as one of the historical towns in Indonesia is rich with architectural and urban heritages; however, there still has no integrated plan to safeguard them. This paper discusses the cultural mapping of the seven heritage conservation districts in the city of Medan. It focuses on exploring the process and challenges of the study from the initial step of data collections to the building of the cultural maps with web based GIS. Multi-method of data collection tactics or triangulation such as field survey, interviews was done to cover the cultural data resources including both tangible (or quantitative) and intangible (or qualitative). Participation of the local community is essential to identify mainly the intangibles one. Based on the preliminary analysis of the seven heritage districts in Medan city, Merdeka-Kesawan area had whole categories of the cultural assets and resources compared to other six heritage areas. Consequently, it influences the enhancement its cultural heritage significance. By using our methods, we emphasized the importance of the cultural mapping in preparing the conservation policies and strategies of the seven heritage districts in Medan.